Residual ISI cancellation for OFDM with applications to HDTV broadcasting. - Dukhyun Kim (IEEE Journal on selected areas in communications)
An iterative technique is developed for orthogonal frequency division multiplexing (OFDM) systems to mitigate the residual intersymbol interference (ISI) that exceeds the length of the guard interval. The technique, called residual ISI cancellation (RISIC), uses a combination of tail cancellation and cyclic restoration and is shown to offer large performance improvements. The effects of imperfect channel estimation are also considered. The RISIC algorithm is applied to a typical terrestrial high-definition television (HDTV) broadcasting system that uses a concatenated coding scheme for error control. Results show that the RISIC algorithm can effectively mitigate residual ISI on static or slowly fading ISI channels